Ability or opportunity to act: What shapes financial well-being?. (April 2020) - Fu, Jonathan
Highlights: The concept of financial well-being serves as a useful indicator for monitoring progress towards SDGs 1, 3, 10, and 16. Representative data on 11 emerging and developed countries is used to measure financial well-being and analyze predictors. The average sample respondent is deficient in over three out of ten metrics considered vital for financial well-being. Sizeable heterogeneity is found in structural and institutional features of financial sectors at country subregion levels. These features are highly predictive of financial well-being, even controlling for individual and subregional covariates. Abstract: This paper draws on nationally representative survey data from 11 emerging and developed economies to measure consumer financial well-being and provide a systematic analysis of its predictors. Whereas the extant literature has been dominated by studies emphasizing the role of individuals' levels of financial literacy and formal financial inclusion, the paper shifts focus towards contextual-level predictors by exploiting subregional variation in structural and institutional features of financial sectors, both within and across countries. It develops a conceptual framework that categorizes such features into 1) those that enhance or inhibit decision-making when selecting or using formal products and 2) those that provide viable substitutes or complements to formal products. It then provides empirical evidence on several examples. Specifically, it highlights the relative importance of having greater prevalence of independent information resources concerning financial products and services, additional provider choice, and some forms of semi-formal and informal finance. The main policy implications are that current efforts to improve broader welfare outcomes through financial literacy and inclusion interventions may still be too narrowly framed. Structural and institutional features related to financial sectors may hinder or enhance financial well-being, even if individuals have adequate financial literacy or be included in formal financial markets. The financial well-being concept may also serve as a useful indicator for monitoring progress towards SDGs 1, 3, 10, and 16.